State formation : anthropological perspectives - Krohn-Hansen, Christian, 1957-; Nustad, Knut G., 1968- (Anthropology, culture, and society., 2005)
What is the 'state' and how can we best study it? This book investigates new ways of analysing the state. The contributors argue that the state is not a fixed and definite object. Our perceptions of it are constantly changing, and differ from person to person. What is your idea of the state if you are a refugee? Or if you are living in post-aparteid South Africa? Our perceptions are formed and sustained by evolving discourses and techniques -- these come from institutions such as government, but are also made by communities and individuals. The contributors examine how state structures are viewed from the inside, by official state bodies, composed of bureaucrats and politicians; and how these state manifestations are supported, reproduced or transformed at a local level. An outline of theoretical approaches is followed by nine case studies ranging from South Africa to Peru to Norway. With a good range of contributors including Cris Shore, Clifton Crais, Ana Alonso and Bruce Kapferer, this is a comprehensive critical analysis of anthropological approaches to the study of state formation.